2012
DOI: 10.1096/fj.12-212183
|View full text |Cite
|
Sign up to set email alerts
|

Fully synthetic polymer vesicles for intracellular delivery of antibodies in live cells

Abstract: There is an emerging need both in pharmacology and within the biomedical industry to develop new tools to target intracellular mechanisms. The efficient delivery of functionally active proteins within cells is potentially a powerful research strategy, especially through the use of antibodies. In this work, we report on a nanovector for the efficient encapsulation and delivery of antibodies into live cells with no significant loss of cell viability or any deleterious effect on cell metabolic activity. This deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…This approach has enabled the delivery of many types of cargos including plasmid DNA, small molecules, antibodies, and small nanoparticles (Lomas et al 2007(Lomas et al , 2008Massignani et al 2010;Canton et al 2013). …”
Section: Exploiting Endocytosis For Nanomedicinesmentioning
confidence: 99%
“…This approach has enabled the delivery of many types of cargos including plasmid DNA, small molecules, antibodies, and small nanoparticles (Lomas et al 2007(Lomas et al , 2008Massignani et al 2010;Canton et al 2013). …”
Section: Exploiting Endocytosis For Nanomedicinesmentioning
confidence: 99%
“…These polymersomes are formed through the self-assembly of amphiphilic copolymers in aqueous media, 7 and combine the advantages of long-term stability with the potential to encapsulate a broad range of cargoes. [8][9][10] We have previously demonstrated that the pH sensitive block copolymer poly(2-(methacryloyloxy) ethyl-phosphorylcholine)-co-poly(2-(diisopropylamino)ethyl methacrylate) (PMPC-PDPA) can combine specific cellular targeting efficiency (through the PMPC block and its affinity toward the scavenger receptor B1), 11 with effective endosomal escape and cytosolic delivery following internalisation (by the pH sensitive PDPA). 8,12 In this study, we describe the half life and bio-distribution of the PMPC-PDPA polymersomes in vivo, showing the dynamics of accumulation within different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…PDPA-based polymersomes have been used for intracellular delivery of DNA (14), antibodies (15), antibiotics (28), anticancer drugs (12,13), and peptides (29). Particularly, for cancer cells, an efficient cytoplasmic delivery improves the drug efficacy (12).…”
Section: Introductionmentioning
confidence: 99%